PENGARUH MODEL PEMBELAJARAN PROJECT-BASED LEARNING (PjBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Sarwati sarwati (Cocos Bio, 2026)
This study aimed to determine the effect of the Project-Based Learning (PjBL) model on students' critical thinking skills in biodiversity material for grade X students at SMAN 1 Masbagik. This study employed a quantitative approach involving an experimental class and a control class. The experimental class was taught using the Project-Based Learning model supported by student worksheets through a herbarium-making project, while the control class was taught using conventional learning methods. The research instrument was a critical thinking skills test in the form of essay questions. The data were analyzed using normality, homogeneity, and t-tests. The results showed that the average pre-test score of the experimental class was 50.19 and increased to 64.60 in the post-test. Meanwhile, the average pre-test score of the control class was 49.50 and increased to 58.17 in the post-test. The t-test results showed that the tcount was 7.0966, which was higher than the ttable of 1.9944 at a 5% significance level. Therefore, H0 was rejected and H1 was accepted. These results indicate that the Project-Based Learning model had an effect on students' critical thinking skills in biodiversity material. PjBL provides students with opportunities to actively engage in observation, investigation, information gathering, discussion, problem solving, and product development activities, thereby supporting the development of critical thinking skills